1988
DOI: 10.1111/j.1471-6402.1988.tb00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Dominance and Inequality in X-Rated Videocassettes

Abstract: Feminists have been concerned about the debasement of women in sexually explicit material. The purpose of this study was to determine the extent of domination and sexual inequality in x‐rated videocassettes through a content analysis of 45 widely available x‐rated videocassettes. The sample was randomly drawn from a list of 121 adult movie titles widely available in family videocassette rental stores in southern California. Over half of the explicitly sexual scenes were coded as predominantly concerned with do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
70
2
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 9 publications
4
70
2
2
Order By: Relevance
“…Our findings are in line with two different strands of research. First, the fact that we found sexually explicit on-line movies to be related with notions of women as sex objects concurs with content analyses that have demonstrated that women are objectified in sexually explicit material (e.g., Brosius et al, 1993;Cowan et al, 1988;Ertel, 1990). This objectification may partly result from men's derogatory sexual comments about women (Cowan et al, 1988;Ertel, 1990).…”
Section: Women As Sex Objectssupporting
confidence: 54%
See 4 more Smart Citations
“…Our findings are in line with two different strands of research. First, the fact that we found sexually explicit on-line movies to be related with notions of women as sex objects concurs with content analyses that have demonstrated that women are objectified in sexually explicit material (e.g., Brosius et al, 1993;Cowan et al, 1988;Ertel, 1990). This objectification may partly result from men's derogatory sexual comments about women (Cowan et al, 1988;Ertel, 1990).…”
Section: Women As Sex Objectssupporting
confidence: 54%
“…First, the fact that we found sexually explicit on-line movies to be related with notions of women as sex objects concurs with content analyses that have demonstrated that women are objectified in sexually explicit material (e.g., Brosius et al, 1993;Cowan et al, 1988;Ertel, 1990). This objectification may partly result from men's derogatory sexual comments about women (Cowan et al, 1988;Ertel, 1990). Second, our result that exposure to audiovisual sexually explicit content on the internet rather than exposure to such content on video or DVD was associated with beliefs that women are sex objects tentatively supports researchers who have argued that, due to its easy accessibility, sexual content on the internet may play a crucial role in the sexual socialization of adolescents (Donnerstein & Smith, 2001;Greenfield, 2004;Thornburgh & Lin, 2002).…”
Section: Women As Sex Objectssupporting
confidence: 54%
See 3 more Smart Citations